2006
DOI: 10.1038/sj.ejhg.5201702
|View full text |Cite
|
Sign up to set email alerts
|

A novel CSX/NKX2-5 mutation causes autosomal-dominant AV block: are atrial fibrillation and syncopes part of the phenotype?

Abstract: The prevalence of congenital heart defects is approximately 1% of all live births. Identifying the genes responsible for cardiac malformation is the first step to understand pathogenesis. Heterozygous mutations in the CSX/NKX2-5 (NKX2E) gene have been identified to cause atrial septal defect (ASD) and/or atrioventricular (AV) conduction disturbance in some families. However, there is great variability in expressivity of the phenotype between the patients with a CSX/NKX2-5 mutation. We screened four sporadic pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
40
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(42 citation statements)
references
References 18 publications
2
40
0
Order By: Relevance
“…Similar to our findings, congenital cardiovascular malformations were previously confirmed in AF patients carrying NKX2-5, GATA4 or GATA6 mutations (45,(51)(52)(53)56,59). Considering some congenital cardiac structural defects may close spontaneously, we cannot rule out the possibility that some mutation carriers had minor cardiac septal defects that closed shortly after birth on their own.…”
Section: Subject Informationsupporting
confidence: 88%
See 2 more Smart Citations
“…Similar to our findings, congenital cardiovascular malformations were previously confirmed in AF patients carrying NKX2-5, GATA4 or GATA6 mutations (45,(51)(52)(53)56,59). Considering some congenital cardiac structural defects may close spontaneously, we cannot rule out the possibility that some mutation carriers had minor cardiac septal defects that closed shortly after birth on their own.…”
Section: Subject Informationsupporting
confidence: 88%
“…In NKX2-5-null mouse embryos, HCN4 was activated in the entire embryonic heart tube, whereas connexin40 expression was inhibited, and ectopic pacemaker cells were observed throughout the heart tube (63). In humans, AF was observed as an isolated phenotype or as a part of compound phenotypes in patients carrying NKX2-5 mutations (45,64,65). Therefore, as a transcriptionally cooperative partner of NKX2-5, GATA5, when a dominant negative mutation occurs, may contribute to the formation of the pulmonary myocardium sleeve and the shift of the pulmonary myocardium to a sinoatrial node-like phenotype by reducing NKX2-5, hence creating an atrial electrophysiological substrate liable to AF.…”
Section: Subject Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…Tbx20 interacts directly with Gata4, Gata5, Nkx2-5 (9), and Tbx5 (10) to regulate gene expression during embryogenesis. Mutations in genes encoding these factors in mice and humans consistently result in an array of structural and conduction cardiac defects of varying severity (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%
“…In agreement with observations in patients, mouse genetics has revealed the complexity of the role of Nkx2-5. [16][17][18][19] Germline deletion of Nkx2-5 gene results in cardiac lethality at the early stages with defects in the myocardial wall thickening, trabeculation, and endocardial cushion formation, suggesting a pro-mitotic role of Nkx2-5. 4,12,13 Recent studies have shown that Nkx2-5 also plays a critical role at chamber ballooning stages.…”
mentioning
confidence: 99%